PEMBERDAYAAN MASYARAKAT MELALUI PENGELOLAAN LIMBAH KOTORAN TERNAK DAN JERAMI PADI MENJADI PUPUK BOKASHI DI DESA KARANGASRI KABUPATEN NGAWI - Putri, Dessy Melia Eka; Widjayanthi, Lenny; Prabawati, Astri Indah; Anandy, Bagus Ervian; Vinola, Erdita (Program Studi Agronomi Fakultas Pertanian Universitas Jember, 2025)
Community empowerment activities were carried out in Karangasri Village, Ngawi Regency, through training on the production of bokashi fertilizer using livestock manure and rice straw waste. This activity aims to improve farmers' knowledge, attitudes, and skills in managing organic waste into economically valuable organic fertilizer. The methods used included socialization, counseling, and hands-on demonstrations involving farmers, the Agricultural Extension Agency (BPP), Babinsa (village security officers), and MSIB students. Evaluation results showed a significant increase in farmers' knowledge about bokashi fertilizer after participating in the activity, as indicated by the comparison between pretest and posttest scores. In addition to raising awareness of waste management, this activity also encouraged farmers to reduce their dependence on chemical fertilizers. This local potential-based empowerment has proven effective in fostering farmer independence and promoting a more sustainable agricultural system